PENGARUH STAD TERHADAP HASIL BELAJAR PKN SISWA KELAS V SEKOLAH DASAR - Bela Herlinda; Tahmid Sabri; Siti Halidjah (Universitas Tanjungpura, 2019)
AbstractThis study purpose to analyze how much influence of the student team achievement divisions model has on the learning outcomes on civic education of the fifth grade students on public elementary school 13 west Pontianak. The method is experimental method with the form of Quasi Experimental Design types of Nonequivalent Control Group Design. The population in the study of all fifth grade students of Pontianak Barat 13 Elementary School, amounting to 72 people, took the sample using purposive sampling technique so that the sample was VA class as the experimental class and VB as the control class. Data collection techniques were measurement techniques, with data collection tools is a test of multiple choice students amounted to 40 questions. Based on data analysis, the result of the average post-test experimental class= 68.93 and average post-test result of the control class= 61,69. The results of hypothesis testing (t-test) obtained t count 3.58 and t table 1,98 (significant level (α) = 5% and dk = 70) which means tcount > ttable, then Ha is accepted. This means there is a significant influence on applying the student team achievement divisions model. From the calculation of Effect Size obtained 0.78 (medium criteria). The student team achievement divisions influences the learning outcomes of civic educations in class V of Elementary School 13 west Pontianak. Key words : Student Team Achievement Divisions, Learning Outcomes, Civic Education.